2020
DOI: 10.1002/csr.2088
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability stewardship: Does roundtable on sustainable palm oil certification create shareholder value?

Abstract: The adoption of sustainability standards is often viewed as a profitability conundrum by palm oil firms and their shareholders. This study examines whether, considering the inherent risk, the Roundtable on Sustainable Palm Oil (RSPO) sustainability initiative creates shareholder value. Based on the panel information of plantation firms listed on the Indonesia and Kuala Lumpur Stock Exchanges, RSPO‐certified firms earned mixed risk‐adjusted performance results relative to non‐RSPO and total palm oil portfolios.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Mixed results were observed in another study of 64 palm oil firms, where Malaysian RSPO-certified firms had poorer risk-adjusted performance than their respective non-certified peers, while the Indonesian RSPO-certified portfolio fared better than its peers, implying RSPO had limited influence on stock performance [37]. Tey and Brindal (2020) [37] identified that RSPO certification requires economies of scale that are more suited for larger farm operations and that palm oil investors may benefit more from small-cap companies in Malaysia. They also raised the need for an easily understood and accepted ESG framework, as opposed to RSPO certification, to provide a more robust view for developing the basis of investing for growth through a sustainability standard.…”
Section: Integrating Sustainability With Financementioning
confidence: 92%
See 3 more Smart Citations
“…Mixed results were observed in another study of 64 palm oil firms, where Malaysian RSPO-certified firms had poorer risk-adjusted performance than their respective non-certified peers, while the Indonesian RSPO-certified portfolio fared better than its peers, implying RSPO had limited influence on stock performance [37]. Tey and Brindal (2020) [37] identified that RSPO certification requires economies of scale that are more suited for larger farm operations and that palm oil investors may benefit more from small-cap companies in Malaysia. They also raised the need for an easily understood and accepted ESG framework, as opposed to RSPO certification, to provide a more robust view for developing the basis of investing for growth through a sustainability standard.…”
Section: Integrating Sustainability With Financementioning
confidence: 92%
“…Climate Advisers also established a palm oil index that found 18 RSPO-certified firms outperforming non-certified counterparts by about 25% over 6.5 years [36]. Mixed results were observed in another study of 64 palm oil firms, where Malaysian RSPO-certified firms had poorer risk-adjusted performance than their respective non-certified peers, while the Indonesian RSPO-certified portfolio fared better than its peers, implying RSPO had limited influence on stock performance [37]. Tey and Brindal (2020) [37] identified that RSPO certification requires economies of scale that are more suited for larger farm operations and that palm oil investors may benefit more from small-cap companies in Malaysia.…”
Section: Integrating Sustainability With Financementioning
confidence: 99%
See 2 more Smart Citations
“…Cluster 1, symbolized in red, includes terms related to studies with the dominant keywords "Government, Governance, Initiative, Actor, Value Chain", for example these keywords discuss studies that lead to how markets interact on a local and international scale [4], corporate sustainability standards may only cover some environmental, social and governance pillars that should be included in sustainable investments [5], certification standards can be improved by including provisions to improve restoration habitat on plantations and smallholder land, the need to increase inclusion and value in sustainable supply chains [6], study of the challenges of certified farmers related to implementing ISPO certification but their marketing activities are still controlled by intermediaries [7], study related to the public policy agenda which focuses more on environmental aspects, aspects of the global poor, as well as public participation and dialogue [8], studies of economic feasibility and competitiveness in developing countries vary but contribute significantly to energy supply [9]. Cluster 2, symbolized in green, consists of studies that tend to lead to almost the same conditions as the previous cluster, there are also several dominant keywords, namely Deforestation, Palm Oil, Policy, Area, Benefit, Use.…”
Section: Network Visualizationmentioning
confidence: 99%